Adult entrances and exits: What does retention literature inform us about urban adult higher educational participants and student success? - Debra Fenty; Jonathan Messemer; Elice Rogers (Adult Education Research Conference, 2016)
This research purpose, derived from a larger study shares findings which help explain retention and, success outcomes associated with Urban adult learners in a 4 year higher educational setting. A critical analysis of the literature reveals in retention, understanding barriers is a key indicator of an institution's effectiveness.
Keywords: urban; adult participation; retention; barriers; higher education